1987
DOI: 10.1002/1097-0142(19871115)60:10<2563::aid-cncr2820601036>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of pain in four cancers

Abstract: Although pain is widely recognized as a major problem in cancer patients, most studies have concentrated on pain among those with advanced or terminal cancer in specialized treatment settings. The study reported here gives a more complete picture of the problem of pain among cancer patients by providing data generalizable to those in early as well as late stages of the disease, and receiving care in the community as well as specialized treatment centers. Having included measures of several distinct features of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
1
3

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(60 citation statements)
references
References 11 publications
2
53
1
3
Order By: Relevance
“…We found that three-fourths of patients suffer some degree of pain and in about one-third of cases this pain does significantly affect daily activities. These figures are consistent with a smaller series of patients with various stages of lung cancer (61 cases with localised disease, 91 with regional, 68 metastatic and 40 with undetermined extension), in which pain was assessed by a graphic rating scale combining visual, numerical and descriptive indicators: only 71 out of 256 patients (27.7%) stated they had had no pain in the last week, while 50.7% had suffered moderate to very bad pain (Greenwald et al, 1987). Overall, these data confirm that pain is an issue of great relevance in the clinical presentation of advanced NSCLC.…”
Section: Discussionsupporting
confidence: 86%
“…We found that three-fourths of patients suffer some degree of pain and in about one-third of cases this pain does significantly affect daily activities. These figures are consistent with a smaller series of patients with various stages of lung cancer (61 cases with localised disease, 91 with regional, 68 metastatic and 40 with undetermined extension), in which pain was assessed by a graphic rating scale combining visual, numerical and descriptive indicators: only 71 out of 256 patients (27.7%) stated they had had no pain in the last week, while 50.7% had suffered moderate to very bad pain (Greenwald et al, 1987). Overall, these data confirm that pain is an issue of great relevance in the clinical presentation of advanced NSCLC.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, differences were observed between pain tolerance and ethnic groups. Therefore, data from this investigation support the observations of earlier studies in nonathletic populations that reported differences between Afro-American subjects, Caucasians, and varying other ethnic groups with respect to pain expression (2,3,4,6,11). However, the confirmation of these observations with the findings of the earlier studies on pain expression and ethnicity (4, 5, 6, 11) may be limited by the terminology, subject population, and subjective measures of pain.…”
Section: Discussionsupporting
confidence: 89%
“…The findings of this recent investigation support the previous observations (2,13,14) that cultures may be associated with specific ethnicity in the expression of pain. In addition, other studies have reported differences in pain expression among ethnic racial populations under varied conditions (4,6,11). The assumption that ethnicity and culture affect an individual's response to pain has been demonstrated with a variety of methods (4,5,11,13,14).…”
mentioning
confidence: 99%
“…If this is implemented consistently and proper palliative approaches are maximised, it has been claimed that effective pain control may be achieved in 80% of cancer patients (Perron and Schonwetter, 2001). However, despite the widespread acceptance of this strategy, more than 40% of prostate cancer patients in routine practice settings report the presence of pain (Greenwald et al, 1987;Portenoy, 1989;Larue et al, 1995;Sandblom et al, 2001).…”
Section: British Journal Of Cancermentioning
confidence: 99%
“…If this is implemented consistently and proper palliative approaches are maximised, it has been claimed that effective pain control may be achieved in 80% of cancer patients (Perron and Schonwetter, 2001). However, despite the widespread acceptance of this strategy, more than 40% of prostate cancer patients in routine practice settings report the presence of pain (Greenwald et al, 1987;Portenoy, 1989;Larue et al, 1995;Sandblom et al, 2001).Health-related quality of life in the final year of life in terminally ill patients, including men with prostate cancer, has been studied previously (Liao et al, 2000;Litwin et al, 2001;Melmed et al, 2002). However, in order to reach a full understanding of how healthrelated quality of life is affected by approaching death, all patients in a population-based sample must be studied.…”
mentioning
confidence: 99%